Anthropometric parameters of elite male runners sprint: are body height and body weight predictors of results - Pavlovic, R.; Mihajlovic, I.; Radulovic, N.; Nikolic, S. (Health, Sport, Rehabilitation, 2022)
Purpose. Athletic sprint runs are cyclical movements of maximum intensity. Speed, reaction time, agility and explosiveness are of special importance in sprinters. The main goal of the research is to determine the influence of Body height (BH) and Body weight (BW) with the best achieved results of in sprint disciplines (60m,100m,200m).